MEMBANGUN KOMPETENSI PEMIMPIN DALAM MENGELOLA ORGANISASI PUBLIK: STRATEGI DAN APLIKASI - Nurul Fitriyah; Agus Suliyadi (Universitas Islam Darul Ulum Lamongan, 2018)
public sector organizations. Competency means capable, capable. Manage competence means leadership skills in managing, managing from planning, coordinating, actualize and oversee public organizations. The competencies that must be owned by the leadership public is at least seven competencies, namely: competence self-manage, competence managing communication, competence of managing plurality, competence of managing ethics, competence managing teams, competing in managing cultural diversity, and competing in managing change. There are at least four strategies to be done: a public leader must think and act generalist, keep learning, put forward an integralistic, strategic way of thinking and oriented to problem solving and public leadership must be fully concentrative. Behavior that must be done public leadership in managing communication is as follows: first,